Influence of light transmission through fiber posts: Quantitative analysis, microhardness, and on bond strength of a resin cement - Luís Fernando Dos Santos Alves Morgan; Marcos Barbosa Pinotti; Fernanda Morais Ferreira; Giovana Mongruel Gomes; Guilherme Costa Silva; Rodrigo De Castro Albuquerque; Allyson Nogueira Moreira (Wolters Kluwer Medknow Publications, 2018)
Context: Light transmission (LT) into deeper areas of the dentin root is limited. Aim: The aim of this study is to perform a quantitative investigation of the radial transmission of light (LT) through different fiber posts and its influence on the Knoop hardness number (KHN) and bond strength (BS) of a dual-cure self-adhesive resin cement at 3 different depths. Materials and Methods: Four types of fiber posts (2 translucent and 2 conventional) were used. LT and KHN analyses were performed in a specially designed matrix, which allowed measurements at 3 different depths. LT was measured using a volt-ampere meter while KHN tests were performed in a microhardness tester. For BS analysis, endodontically treated bovine roots were divided into 4 groups, each group receiving one type of post. After cementation, cross sections of the root were tested for resistance to displacement using a universal testing machine. Statistical Analysis Used: Statistical analysis was performed by using this ANOVA and Tukey's test. Results: For LT, translucent posts showed significantly higher values at all depths compared to the conventional ones. For all posts, LT decreased at the deeper depths. The KHN results showed no statistical differences among the different posts, regardless of depth. For BS, a translucent post showed the highest values, and comparative analyses between the different depths of posts also showed statistically significant differences while comparisons among the different depths of the same post showed no differences. Conclusions: LT depended on the type of post and on depth. The type of post did not significantly influence the cement KHN. A translucent post showed higher BS in pooled data.